'Lean on me': an integrative literature review on the middle management role in lean. (17th February 2022) - Reynders, Philipp; Kumar, Maneesh; Found, Pauline
Abstract : Leadership makes or breaks a lean transformation while mismanagement at the middle management level is likely to impede lean sustainability in particular. Although the role of leadership is widely acknowledged in lean, the middle management role remains fragmented in the literature with a limited focus to date. Taking this into account, the purpose of this paper is to gain a holistic view of the middle management role in lean and its influence on organisational transformation. An integrated literature review methodology was adopted to develop an integrated, conceptual model of the middle management role in lean. The results demonstrate that middle managers are protagonists in lean evolution and indispensable for sustainable success. In acting as cultural change agents, middle managers promote continuous improvement and conduce the transition towards a lean organisation through managerial push and soft lean evolvement, shaping and maintaining a continuous improvement-orientated culture by engaging, inspiring and enthusing the wider workforce. The integrative literature review contributes with a six-point integrative, conceptual model of the middle management role in lean, including policy deployment, leader standard work, continuous improvement promotion, self-development, coaching and gemba walks.